2000
DOI: 10.1097/00000539-200003000-00027
|View full text |Cite
|
Sign up to set email alerts
|

What Concentration of Sufentanil Should be Combined with Ropivacaine 0.2% wt/vol for Postoperative Patient-Controlled Epidural Analgesia?

Abstract: Sufentanil is added to epidural infusions of ropivacaine 0.2% wt/vol to improve the effectiveness of postoperative pain management. Regarding the risk of side effects, however, it is still unclear what concentration of sufentanil should be added to the local anesthetic. For postoperative thoracic epidural analgesia after major abdominal surgery, the combination of ropivacaine 0.2% wt/vol and 0.75 microg/mL sufentanil resulted in an appropriate cost:benefit ratio between good analgesia and side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(24 citation statements)
references
References 15 publications
2
18
0
4
Order By: Relevance
“…Group R-6 (circles), 6 mg·h −1 ropivacaine; group R-9 (squares), 9 mg·h −1 ropivacaine; group R-12 (triangles), 12 mg·h −1 ropivacaine; group R-18 (crosses), ropivacaine 18 mg·h −1 . The infusion dose was maintained for 24 h after surgery and then was reduced to half from 24 to 48 h. *P < 0.05 compared to group R-6; † P < 0.05 compared to group R-9; ‡ P < 0.05 compared to group R-12 ral analgesia with a combination of anesthetics and opioids is the gold standard for pain relief after thoracic surgery [2,3,6,8,9], epidural opioids sometimes cause side effects such as nausea, respiratory depression, pruritus, and sedation [4][5][6]. Gottschalk et al [10] demonstrated that a thoracic epidural infusion of 0.375% ropivacaine alone was equivalent to a combination of 0.125% bupivacaine and sufentanil in terms of analgesic effect, without increasing the incidence of side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Group R-6 (circles), 6 mg·h −1 ropivacaine; group R-9 (squares), 9 mg·h −1 ropivacaine; group R-12 (triangles), 12 mg·h −1 ropivacaine; group R-18 (crosses), ropivacaine 18 mg·h −1 . The infusion dose was maintained for 24 h after surgery and then was reduced to half from 24 to 48 h. *P < 0.05 compared to group R-6; † P < 0.05 compared to group R-9; ‡ P < 0.05 compared to group R-12 ral analgesia with a combination of anesthetics and opioids is the gold standard for pain relief after thoracic surgery [2,3,6,8,9], epidural opioids sometimes cause side effects such as nausea, respiratory depression, pruritus, and sedation [4][5][6]. Gottschalk et al [10] demonstrated that a thoracic epidural infusion of 0.375% ropivacaine alone was equivalent to a combination of 0.125% bupivacaine and sufentanil in terms of analgesic effect, without increasing the incidence of side effects.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used ropivacaine as the local anaesthetic and sufentanil as the opioid. Ropivacaine was the local anaesthetic of choice because of more differential block allowing for a better separation between sensory and motor block, low toxicity relative to potency and long duration of action, resulting in a low risk of toxicity during continuous infusion [11]. Sufentanil has a rapid onset and potent analgesic effect due to high lipid solubility, an intermediate degree of ionisation, a low molecular weight, a very high m receptor affinity, and a high therapeutic range [5,12].…”
Section: Discussionmentioning
confidence: 99%
“…better coughing). Not only systemically but also epidurally applied opioids lead to detectable, but interindividually highly variable opioid plasma concentrations (Hansdottir et al 1996;Brodner et al 2000). In the large majority of clinical studies, opioid plasma concentrations were not determined.…”
Section: Acute Postoperative Pain Therapymentioning
confidence: 99%